Note sull'epistolario di Francesco Ciceri (1527-1596) (Quaderni di Gargnano, 2018)
This paper presents the Italian and Latin correspondence of the Swiss-born Humanist Francesco Ciceri. After a short biographical introduction to Ciceri, the paper turns its attention to the dense network of contacts between the author and important figures of his time, notably Ciceri's mentor, Marco Antonio Maioragio, and the Basel-based printer, Johannes Oporinus. The paper therefore places Ciceri at the heart of the cultural and literary exchange between northern Europe and the Italian-speaking world. The paper also discusses the irreverent “lettera burlesca” genre, using examples of Ciceri’s writing for the purpose.
Keywords: Umanesimo; Bibliofilia; Marco Antonio Maioragio; Johannes Oporinus; lettera burlesca